El Excentrico, 1954-04-05 - Garcia, Humberto:::Publisher:::::::::::: (San Jose, California; Garcia Printing, 2023)
April 5, 1954 [5 de abril de 1954]. Anos 4, No. 11. Cover has a photo of Juanita Martinez, also known as "Kikes" in bridal attire. She got married prior to this issue's release. The headline reads, "The former Juanita 'Kikes' Martinez."